Decolonizing Nature? Dominant Worldviews and Worldviews of Agroecological Farmers in Germany to Address the Global Environmental Crisis - Hirsch, Jennifer; Justus Liebig University Giessen (My University, 2022)
A culture‘s agriculture is highly expressive of its fundamental value and knowledge systems. As a central interaction between humans and nature, it reflects both people’s self-conceptions and the relationships with their environment. Industrial agriculture emerges from the classical Western separation of humans and nature. As a result of this dualism, nature becomes either an untouchable, contemplative sanctuary or an exploitable resource - the value of which is measured in both cases by its utility to humans. This modern, respectively colonial way of thinking justifies power relations and stabilizes dynamics of domination between humans, animals and nature. Agroecological approaches and practices are based on a renegotiation of these fundamental relationships and on a holistic understanding of nature. Yet, globally, agroecology as a social movement is still restrained and largely unexplored in the Global North. We know little about the ontological foundations and cultural beliefs of agroecological farmers in Western Europe. This thesis therefore investigated the worldviews and conceptions of nature of agroeological farmers in Germany as part of a modern society and Western culture that fosters a reductionist view on nature and a corresponding productivist approach to farming. In particular, the research goal was to discern whether the four interviewees employ a decolonized perspective in their relationships with nature, and to further identify which roles they assign themselves based on their cosmovisions and in the face of societal challenges such as the climate crisis. The results of the qualitative reconstructive interview study show an ambiguity in the form of complexly interwoven and partly conflicting co-existences of colonial and decolonial elements within the farmers’ worldviews, indicating a transformational process. At the same time, the analysis revealed effects of sociocultural imprints on transformational potentials and thus brought to light underlying ontological hurdles to an agroecological transition.
Keywords: agroecological transition; ontology; Western paradigm; human-nature relationships; decolonization; ddc:300; ddc:333.7; ddc:630